The role of business accelerators as catalysers of food systems transformations in East and Southern Africa - Lozano, Denise; Nguvi, Caroline; Peterson, Nathanial; Dam Lam, Rodolfo; Brako Dompreh, Eric; Manyise, Timothy; Rossignoli, Cristiano (Frontiers Media S.A., 2025)
The transformation of global food systems is essential for achieving the Sustainable Development Goals (SDGs) and fulfilling the Paris Agreement commitments, especially in vulnerable regions like East and Southern Africa (ESA). In such regions, small and medium enterprises (SMEs) across food systems value chains can drive transformative innovations, but often require external support to build capacity. Business accelerators, originally from the corporate and tech sectors, have emerged as key players in supporting early-stage ventures, yet their role in agriculture and food systems remains underexplored. This paper presents findings from the first cohort of the CGIAR Food Systems Accelerator (CFSA), which supports agribusinesses in ESA in scaling climate-smart innovations. Through its science-backed, tailored approach, CFSA enhances investment readiness and technical capabilities among SMEs. The assessment, based on interviews with agribusiness founders (n = 10), reveals perceived improvements in entrepreneurial skills, partnership opportunities, and organizational capabilities, though challenges related to financial constraints and enabling environment remain. This study highlights the potential of non-profit accelerators in fostering food systems transformation through SME development, with important implications for poverty reduction, food security, and climate adaptation. Expanding such programs and studying their long-term impacts is crucial for driving sustainable growth in food systems in the Global South.